Enhanced living environments : from models to technologies - Goleva, Rossitza I.; Ganchev, Ivan (Telecommunications engineer); Dobre, Ciprian; Garcia, Nuno M.; Valderrama, Carlos (The Institution of Engineering and Technology, 2017)
The book reviews developments in the following fields: enhanced living environments; socioecological psychology; pervasive sensing; social connectedness; information ethics; communication ethics; smart personal environments; stress-level monitoring; Big Data healthcare system; healthcare information searching; Internet; wireless body area networks; AALaaS platform; ELEaaS platform; linear wireless sensor networks; protocols; next-generation networks; cyber-physical systems; health monitoring; wearable healthcare; and after-stroke home rehabilitation.
Keywords: Ambient intelligence.; Congregate housing.; Computer network protocols.; End-user computing.; Entertainment computing.; Self-help devices for people with disabilities.; Telecommunication in medicine.; Artificial intelligence.; Wireless communication systems.; elektronické knihy; electronic books